An Investigation on Heavy Metal Concentration in Tree Barks at Areas Affected by the 2015 Haze in Malaysia - Shahrom, Marsha Daeyana (IRC, 2016)
Haze has been occurring annually due to forest burning in Indonesia and this has affected countries in the South East Asia region including Malaysia. The Air Pollutant Index (API) is used as an indicator of air pollution in Malaysia which includes the measurement of five major pollutants; ozone (O3), carbon monoxide (CO), nitrogen dioxide (NO2), sulphur dioxide (SO2) and particulate matter with a diameter of less than 10 micron (PM10). However, the measurement of heavy metals are not indicated in API although past research have shown that the haze also contains several elements that is high in concentration. It is thus crucial to identify the concentration of heavy metals brought by the haze as it possesses harmful effects to the public health and the environment. Therefore, this study suggests the use of a biomonitoring technique using tree barks as it has shown to be a reliable indicator of pollutants based on its ability to accumulate particulate matter containing heavy metals over time. These bioindicators can then be used to measure the concentration of heavy metals deposited specifically Zn, Pb, Fe, Ni, and Cu.